GEORGE ANTONIU, OUTSTANDING PERSONALITY OF THE ROMANIAN CRIMINAL SCIENCES - DUVAC, Constantin (International Journal of Legal and Social Order, 2022)
First, the author reviews the main biographical milestones of his former professor, as well as his main works and scientific activities. Then, the author analyzes in detail the main ideas of University Professor Ph.D. George Antoniu that contributed to the development of the science of criminal law in Romania, stressing the ones that turned into positive criminal law rules. In this regard, the work of University Professor Ph.D. George Antoniu represented, in numerous cases, soursces of inspiration for the Romanian criminal legislator, his thesis being largely recognized as such by the authors of criminal law from our country.